2022
DOI: 10.1177/10732748221111296
|View full text |Cite
|
Sign up to set email alerts
|

Tislelizumab: A Modified Anti-tumor Programmed Death Receptor 1 Antibody

Abstract: Tislelizumab is an anti-programmed death receptor 1 (PD-1) monoclonal immunoglobulin G 4 antibody developed by BeiGene. The structure of tislelizumab has been modified to maximally inhibit the binding of PD-1 to programmed death ligand 1 (PD-L1) and minimize the binding of tislelizumab to Fcγ receptors. In clinical studies, tislelizumab has shown preliminary anti-tumor effects in various solid tumors, such as Hodgkin’s lymphoma, urothelial carcinoma, lung cancer, gastric and esophageal cancer, liver cancer, na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 70 publications
0
20
0
Order By: Relevance
“…Several clinical trials have reported encouraging antitumor activity and manageable TRAEs in patients with advanced solid tumors who underwent tislelizumab treatment ( 25 , 26 ). Furthermore, tislelizumab has been included in the medical insurance catalogue in China, which reduces its price ( 14 ). Thus, it may prove to be an efficient and cost-effective PD-1 inhibitor for the treatment of advanced CC, and this warrants further study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several clinical trials have reported encouraging antitumor activity and manageable TRAEs in patients with advanced solid tumors who underwent tislelizumab treatment ( 25 , 26 ). Furthermore, tislelizumab has been included in the medical insurance catalogue in China, which reduces its price ( 14 ). Thus, it may prove to be an efficient and cost-effective PD-1 inhibitor for the treatment of advanced CC, and this warrants further study.…”
Section: Discussionmentioning
confidence: 99%
“…Tislelizumab, a humanized immunoglobulin (Ig) G4 monoclonal antibody with high specificity and affinity for PD-1, was engineered to minimize the binding of Fcγ receptors on macrophages. It reduces antibody-dependent phagocytosis, which is thought to be the mechanism underlying T-cell clearance and resistance to anti-PD-1 therapy ( 14 ). Given its favorable antitumor activity and tolerance, tislelizumab has been approved by the U.S. Food and Drug Administration (FDA) for the treatment of esophageal cancer, hepatocellular carcinoma, and gastric/gastroesophageal junction cancer ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…They can block PD-1/PD-L1 interaction, activate T cells, and restore their anti-tumor immune response. [ 3 ] Tislelizumab [ 4 , 5 ] is a humanized monoclonal antibody against PD-1(IgG4 variant) that was independently developed in China. Its antibody structure differ from that of the traditional PD-1 antibody.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, some researchers have tried to use tislelizumab for refractory renal cell carcinoma, cholangiocarcinoma, and serous endometrial carcinoma, all of which have achieved good therapeutic effects. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the efficacy of combination therapy was not evaluated because the patient refused chemotherapy. Tislelizumab, an anti-PD-1 antibody developed in China that has a different structure to that of traditional anti-PD-1 antibodies ( 21 ), produced an ORR of 13% (32/249) in HCC patients regardless of the number of prior lines of treatment ( 22 ). Chao et al.…”
Section: Discussionmentioning
confidence: 99%